2017
DOI: 10.37358/rc.17.9.5822
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Antioxidant Effect and Antimicrobial Efficacity of Propolis, Myrrh and Chlorhexidine as Beneficial Toothpaste Components

Abstract: Toothpastes containing different components which could have beneficial effects on oral health and the identification of better composition are always a research challenge. Our study aims are to evaluate the synergistic effect of propolis, myrrh, and chlorhexidine, separated and combined in some formulated toothpaste. To assess the electrochemical capacity by monitoring of physico-chemical parameters (pH conductivity), the mixture of these components in toothpaste into artificial saliva solution was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Myrrh as a traditional medicine has been used since ancient times. In modern times, myrrh is used as an antiseptic in topical and toothpaste [27]. It has been shown that some sesquiterpene components of myrrh, including furanodien-6-one, methoxyfuranoguai-9-en-8-one possess in vitro bactericidal, and fungicidal activity against multiple pathogenic bacteria, including E. coli , S. aureus , P. aeruginosa , and C. albicans [28], but these two most active compounds were not detected in our samples [19] (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Myrrh as a traditional medicine has been used since ancient times. In modern times, myrrh is used as an antiseptic in topical and toothpaste [27]. It has been shown that some sesquiterpene components of myrrh, including furanodien-6-one, methoxyfuranoguai-9-en-8-one possess in vitro bactericidal, and fungicidal activity against multiple pathogenic bacteria, including E. coli , S. aureus , P. aeruginosa , and C. albicans [28], but these two most active compounds were not detected in our samples [19] (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial and fungal suspensions were uniformly inoculated on the surface of the culture media distributed in Petri dishes. Sterile cylinders, made of stainless steel, with a height of 10 mm and an inside diameter of 5 mm, were deposited on the surface of the sown plates [6,9]. The samples to be analysed, obtained by dissolving the substances in DMSO at a concentration of 25 µg/mL, were deposited inside the sterile cylinders in volume of 100 µL, the final tested concentration being of 2.5 µg.…”
Section: Evaluation Of the Antimicrobial Potential Of New Isoniazid Derivativesmentioning
confidence: 99%
“…The test results of antibacterial effect of zinc zeolite toothpaste are shown in table 3. According to literature [5,11], the Staphylococcus aureus and Escherichia coli antibacterial rate can reach 99.9% when the zinc zeolite mass fraction exceeds 2%. The quality score of the sample toothpaste zinc zeolite is 5%.…”
Section: Antibacterial Effect Of Zinc Zeolite Toothpastementioning
confidence: 99%